2014
DOI: 10.1002/cyto.a.22455
|View full text |Cite
|
Sign up to set email alerts
|

Standardized flow cytometry assay for identification of human monocytic heterogeneity and LRP1 expression in monocyte subpopulations: Decreased expression of this receptor in nonclassical monocytes

Abstract: In this article, we present a flow cytometry assay by which human blood monocyte subpopulations-classical (CD14 11 CD16 2 ), intermediate (CD14 11 CD16 1 ), and nonclassical (CD14 1 CD16 11 ) monocytes-can be determined. Monocytic cells were selected from CD45 1 leukocyte subsets by differential staining of the low-density lipoprotein receptor-related protein 1 (LRP1), which allows reducing the spill-over of natural killer cells and granulocytes into the CD16 1 monocyte gate. Percentages of monocyte subpopulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…To determine whether Wnt expression was induced by inflammatory stimulation, we stimulated a monocyte cell line, RAW 264.7, and human monocytes with TNF. Human monocytes were identified using previously described methods (Supplementary Figure 2 and Supplementary Methods, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40468/abstract). After conducting a cytotoxicity assay (Supplementary Figure 3, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40468/abstract), we defined doses of 1 ng/ml and 10 ng/ml TNF as low‐intensity inflammatory stimulation and a dose of 50 ng/ml TNF as high‐intensity inflammatory stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether Wnt expression was induced by inflammatory stimulation, we stimulated a monocyte cell line, RAW 264.7, and human monocytes with TNF. Human monocytes were identified using previously described methods (Supplementary Figure 2 and Supplementary Methods, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40468/abstract). After conducting a cytotoxicity assay (Supplementary Figure 3, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40468/abstract), we defined doses of 1 ng/ml and 10 ng/ml TNF as low‐intensity inflammatory stimulation and a dose of 50 ng/ml TNF as high‐intensity inflammatory stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…As a possible limitation regarding the monocyte analysis, it should be mentioned that although the great majority of natural killer (NK) cells are confined to the lymphocyte population (based on forward-and sidescatter properties in flow cytometric analysis) we cannot exclude the possibility that some CD16 1 NK cells may be present in the monocyte gate. To avoid this potential error source, future studies should include a pan-monocyte marker, as was suggested recently [54].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this potential error source, future studies should include a pan-monocyte marker, as was suggested recently [54]. In light of our finding that in sarcoidosis patients ICOS high T regs are detected in the inflamed lungs, and that this is accompanied by an increased proportion of non-classical monocytes which over-express ICOS-L, we hypothesize that the ICOS/ICOS-L axis might indeed be involved critically in the regulation of ongoing T cellmediated inflammation in the lung.…”
Section: Cd4mentioning
confidence: 99%
“…Non-adherent cells were removed and the adherent cells were washed twice with phosphate-buffered saline. Following washing >75% of the cells were identified as monocytes, as assessed by FACS Calibur flow cytometry (BD Biosciences) using R-phycoerythrin-conjugated anti-human CD14 IgG antibody (BioLegend, Inc., London, UK) (26).…”
Section: Methodsmentioning
confidence: 99%